2011
DOI: 10.1038/gene.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

IRF7: activation, regulation, modification and function

Abstract: Interferon regulatory factor 7 (IRF7) was originally identified in the context of Epstein–Barr virus (EBV) infection, and has since emerged as the crucial regulator of type I interferons (IFNs) against pathogenic infections, which activate IRF7 by triggering signaling cascades from pathogen recognition receptors (PRRs) that recognize pathogenic nucleic acids. Moreover, IRF7 is a multifunctional transcription factor, underscored by the fact that it is associated with EBV latency, in which IRF7 is induced as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
449
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(466 citation statements)
references
References 241 publications
(305 reference statements)
11
449
2
4
Order By: Relevance
“…Viral protein level expression was verified by immunoblotting to ensure that the lack of inhibition was not due to a lack of protein expression. TBK1 activates IRF7 in addition to IRF3 (51,52). It was shown previously that MC159 does not inhibit IRF7-induced IFN-β enhancer activation (43) when a constitutively active IRF7 is expressed, suggesting that MC159 does not directly interact with IRF7.…”
Section: Resultsmentioning
confidence: 99%
“…Viral protein level expression was verified by immunoblotting to ensure that the lack of inhibition was not due to a lack of protein expression. TBK1 activates IRF7 in addition to IRF3 (51,52). It was shown previously that MC159 does not inhibit IRF7-induced IFN-β enhancer activation (43) when a constitutively active IRF7 is expressed, suggesting that MC159 does not directly interact with IRF7.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that human plasmacytoid dendritic cells (pDCs) can express IRF7 constitutively, but this basal expression is rapidly upregulated after the stimulation and is maintained in vitro only in the presence of a stimulant. Further studies have demonstrated that nuclear translocation of IRF7 occurs earlier than IRF7 induction (Au et al, 1998;Sato et al, 1998;Honda et al, 2005;Ning et al, 2011). The characterisation of cellular components involved in viral detection and IRF activation will further delineate this vital mechanism of the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, extensive studies of the interferon regulatory factor (IRF) family have confirmed that IRFs have gained great attention due to their diverse roles such as initiating antiviral responses, regulating inflammatory cytokine expression and controlling cell cycle and apoptosis, as well as mediating the development of macrophages, dendritic cells, B and T lymphocytes (Au et al, 1998;Sato et al, 1998;Honda et al, 2005;Ning et al, 2011). As an important transcription mediator, IRF7 has been initially identified to induce the expression of IFNs and IFN-stimulated genes (ISGs) in the hosts, and it plays a critical role in initiating host innate immune responses to viral and bacterial infection (Marie et al, 1998;Smith et al, 2001).…”
mentioning
confidence: 99%
“…Distinct from both KSHV and MHV-68 encoded ORF36 can only bind to phosphorylated IRF3, and inhibits the production of IFN-β (Hwang et al, 2009), EBV encoded ORF36 (namely BGLF4 kinase) could phosphorylates IRF-3 and inhibits the active IRF-3 recruitment to ISREs and thus suppresses the type I IFN response (Wang et al, 2009). Similar to IRF-3, IRF-7 is also phosphorylated by TBK1 and IKKε, which leads to heterodimerize with IRF-3 and fully stimulate type I IFN expression (Ning et al, 2011). It has been shown that although ORF45 of KSHV could inhibit IRF-7 phosphorylation (Zhu et al, 2002;Liang et al, 2012), the latent membrane protein LMP1 induces the phosphorylation and K63-linked ubiquitination of IRF7, resulting in its nuclear translocation and increased transcriptional activity (Ning et al, 2008;Bentz et al, 2012).…”
Section: Phosphorylation-mediated Viral Regulation Of Interferon Regumentioning
confidence: 99%